Avaliação das alterações no número de cópias de DNA genômico total em ameloblastoma, carcinoma ameloblástico e tumor odontogênico adenomatóide - Alessandra Pires Duarte (2016)
The pathogenesis of odontogenic tumors is closely related to odontogenesis, tooth formation process. Among epithelial odontogenic tumors, there are the ameloblastoma and the adenomatoid odontogenic tumor (AOT). The ameloblastoma surgical treatment can lead to patient morbidities. AOT and unicystic ameloblastoma have a less aggressive behavior, since they are encapsulated. The ameloblastomas malignant counterpart, ameloblastic carcinoma, is a rare malignant neoplasia with uncertain pathogenesis. Copy Number Variants (CNV) is a genomic structural alteration (deletion or duplication) larger than one kilobase (Kb) that may be involved in the molecular pathogenesis of neoplasias. The aim of this study was to identify CNVs in these epithelial odontogenic tumors and to evaluate possible differences on the CNVs profiles among the four tumor subtypes included in this study (unicystic ameloblastoma, multicystic ameloblastoma, AOT and ameloblastic carcinoma). In addition, we identified the rare CNVs and the genes involved that could be possible candidates for the pathogenesis of the tumors. Twelve samples (unicystic ameloblastoma, n=3;pathogenic multicystic ameloblastoma, n=4; ameloblastic carcinoma, n=1; e AOT, n=4) were included. CNVs were analyzed by using the ultra-high resolution CytoScan-HD array (Affymetrix), a platform that uses polymorphic (SNPs) andnon-polymorphic probes covering the whole genome. 81 alterations werefound between losses, gains and copy neutral loss of heterozygozity, cnLOH. Only seven alterations were considered rare. No specific differences were observed in the CNVs profiles among the groups of tumors. Some of the rare alterations encompass genes that are potentially candidates in the tumor pathogenesis and for personalized medicine, such as PPP2R5A, B4GALT1, SPINK4 and BAG1 genes in unicystic ameloblastoma and IGF2BP3 gene in AOT.